2010
DOI: 10.1007/s12020-009-9304-x
|View full text |Cite|
|
Sign up to set email alerts
|

Macroprolactinemia, like hyperprolactinemia, may promote platelet activation

Abstract: Insulin resistance, which provides a convenient milieu for platelet activation, has been closely associated with atherosclerotic disorders. Although it often accompanies hyperprolactinemia, findings conflict concerning its clinical impact in macroprolactinemia. In order to investigate the relationship between hyperprolactinemia and platelet activation evidenced by ADP-stimulated P-selectin expression on flow cytometry, we studied hyperprolactinemic, macroprolactinemic, and normoprolactinemic subjects. Thirty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…However, almost all of these studies included fewer than 30 patients with hyperprolactinemia. Therefore, the strength of the current study is its large sample size of approximately 100 men and women with hyperprolactinemia, which is nearly three times that of any previous study 27,28…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, almost all of these studies included fewer than 30 patients with hyperprolactinemia. Therefore, the strength of the current study is its large sample size of approximately 100 men and women with hyperprolactinemia, which is nearly three times that of any previous study 27,28…”
Section: Discussionmentioning
confidence: 97%
“…Erem et al27 reported that the levels of fibrinogen and antithrombin III among patients with prolactinoma were significantly increased compared with control participants. Similarly, Anaforoglu et al28 found that adenosine diphosphate (ADP)-stimulated expression was significantly greater in the hyperprolactinemia group than in the control group; this ADP-stimulated expression provides evidence of platelet activation. Based on these findings, prolactin is regarded as a hormone-associated coagulant, and patients with hyperprolactinemia are considered at risk for VTE.…”
Section: Introductionmentioning
confidence: 86%
“…Anaforoglu et al (47) studied platelet activation looking at P-selectin expression in hyperprolactinemic, macroprolactinemic, and normoprolactinemic subjects, matched regarding blood pressure, plasma lipids, waist circumference, and insulin sensitivity status. Platelet activation was greater in hyperprolactinemic and macroprolactinemic patients.…”
Section: Controversies and Areas Of Uncertaintymentioning
confidence: 99%
“…The possible negative effect of macroprolactin is still controversial. Anaforoglu et al showed that a group of patients with monomeric hyperprolactinemia and macroprolactinemia compared to a group with normoprolactinemia demonstrated greater platelet activation and atherosclerotic disorders [92]. Further research is necessary to elucidate the potential biological effect of macroprolactin and its treatment requirement.…”
Section: Management Of Macroprolactinemiamentioning
confidence: 99%